2002
DOI: 10.1115/1.1498264
|View full text |Cite
|
Sign up to set email alerts
|

Optical Measurements of Shrinkage in UV-Cured Adhesives

Abstract: This paper describes an optical method that has been developed to accurately measure shrinkage during the cure of adhesives treated with UV light. The experiment was designed to measure changes in the volume of very small quantities of material appropriate to uses in the fiber-optic and micro-electronic industries. A spot-curing device (EFOS Inc.) was used to deliver a controlled exposure of UV-light with a known distribution of wavelengths to the sample. The results indicate that reproducible values for the v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(12 citation statements)
references
References 3 publications
0
11
0
Order By: Relevance
“…Global polymerization shrinkage of the resists upon UV curing was measured using a simple method suggested by Hudson et al 51 In this method a ∼20 μL droplet of a resist is placed on a hydrophobic surface and the sessile volume of the droplet was measured before and after UV shining with a UV lamp at an intensity of 1.8 W/cm 2 for 10 s. In order to exclude any evaporation contribution to the shrinkage measurements, the volume of a droplet of uncured resists was measure over a 5 min time period and showed no measurable change. Therefore, the decrease measured in the volume after curing is solely attributed to the curing shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…Global polymerization shrinkage of the resists upon UV curing was measured using a simple method suggested by Hudson et al 51 In this method a ∼20 μL droplet of a resist is placed on a hydrophobic surface and the sessile volume of the droplet was measured before and after UV shining with a UV lamp at an intensity of 1.8 W/cm 2 for 10 s. In order to exclude any evaporation contribution to the shrinkage measurements, the volume of a droplet of uncured resists was measure over a 5 min time period and showed no measurable change. Therefore, the decrease measured in the volume after curing is solely attributed to the curing shrinkage.…”
Section: Methodsmentioning
confidence: 99%
“…During the long post-cure cycle, most adhesives that have been gelled only, will relax as they begin to heat, and transform into a fully cross-linked polymer only after passing through a period of lower viscosity and relaxation. 25 …”
Section: Curing Shrinkagementioning
confidence: 97%
“…During the curing, monomer molecules are converted into a cross-linked polymer network, replacing van der Waals spaces between monomers with smaller covalent bond spaces. Resistance to polymerization shrinkage due to cross-linking by thermal or ultraviolet (UV) curing needs to be considered for precise manufacturing [ 18 , 19 ]. Existing studies on NIL resistance to shrinkage showed that shrinkage can reach up to 20% depending on the mold pattern size [ 20 , 21 ].…”
Section: Introductionmentioning
confidence: 99%